(untitled) (Mongolian Journal of Agricultural Sciences, 2023)
The paper aims to develop the on-site diagnostic parameters for assessing the operation of engines through the content (g/ton) of wear elements and contaminants in used oil. Here, it refers to heavy-machinery vehicles used in various industries of Mongolia such as agriculture, railway, building and road construction, mining etc. This study analyzed the results of measurements in the used oil samples from 20 diesel engines over a maintenance period of 5-6 years using spectral analysis. It focuses on three key goals: determining the content of wear elements and contaminants in used oil (g/ton), studying the intensity of engine wear during one period of maintenance, and using non-parametric statistical methods to develop the on-site diagnostic parameters based on the concentration of wear elements and contaminants in the samples of used oil. The diagnostic parameters determined as a result of this study can enable technicians to perform diesel engine maintenance based on the actual technical condition of the engine, rather than relying solely on the manufacturer’s recommended maintenance schedule, reduce the repair cost by addressing the aspects before serious breakdowns or delays occur and improve overall the engine performance, resulting in significant benefits for the transportation and heavy-machinery industries.